Current Clinical Profile of Enteric Fever in a Teaching Hospital (TAJ: Journal of Teachers Association, 2009)
This study was designed to assess the current of clinical presentations, complications andprognosis of enteric fever cases in Bangladeshi population and also to assess the antimicrobialsensitivity of the causative organisms. A total of 65 patients, with either fever of any durationwith positive blood culture for Salmonella, of fever of more than a week with strong clinicalevidence of enteric fever along with single Widal titre TO >160 of AO >160 or BO> 160, wereselected from indoor medical wards of Rajshahi Medical College Hospital from August 2000 toMay 2001. Blood culture with sensitivity pattern, Widal tests and relevant investigations weredone in all patients. Majority (87.70%) of the patients presented on the second or third week oftheir illness. Other clinical profiles of the patients were comparable to different studies done inour country and in abroad. Common complications were pneumonia, meningitis and typhoidpsychosis. Isolated salmonellae from blood culture were 100% sensitive to Ciprofloxacin andPefloxacin. Two out of sixty five patients (3.07%) expired due to complications.doi: 10.3329/taj.v15i2.3914TAJ December 2002; Vol.15(2): 81-83